Peningkatan Pemahaman Remaja Tentang Bakteri Ropionibacterium Acnes Bagi Kesehatan Kulit - Rindi Novitri Antika (Universitas Lancang Kuning, 2020)
This dedication activity aims to increase the knowledge of adolescents about Propionibacterium acnes bacteria for skin health, especially acne, and form the awareness of adolescents to maintain and enhance the level of personal health. The specific target is for teenagers to be aware of how to maintain healthy skin, especially the face, remembering that adolescence is a period where their activities are very high, like activities outside the home, often forgetting to clean faces exposed to dust and dirt, as well as hormonal changes that affect the physiological of the body. This activity also provides knowledge about the bacteria Propionibacterium acnes, ranging from understanding, characteristics to the mechanism of action of bacteria. The methods and techniques of socialization consist of stages: planning, action, and reflection. 1) planning is carried out with the preparation and socialization of the program; 2) action, i.e. the implementation phase of the service, begins with exposure to the bacterium Propionibacterium acnes, the mechanism of action of the bacteria and its relation to skin health, then proceed with a question and answer session; 3) reflection, done by analyzing the participants' responses to the activities that have been carried out.